2008
DOI: 10.1016/j.ejheart.2008.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Changes in myocardial electrical impedance in human heart graft rejection

Abstract: Background: Monitoring of post-transplant heart rejection is currently based on endomyocardial biopsy analysis. This study aimed to assess the effects of heart graft rejection on myocardial electrical impedance. Methods and results: Twenty-nine cardiac transplant patients and 9 controls underwent measurement of myocardial electrical impedance using a specifically designed amplifying system. The module and phase angle of myocardial impedance were measured. Histopathological rejection grading was performed accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 9 publications
0
14
0
1
Order By: Relevance
“…In contrast, during the healing over process the necrotic scar turns to lower than normal impedance values (Fallert et al, 1993; Wolf et al, 2001; Salazar et al, 2004). In these studies, the technique of measuring the changes in myocardial impedance did not allow to delineate the sequential impedance variations elicited during the systole and diastole phases of the cardiac cycle because of the long time required for the whole impedance spectrum acquisition (Gersing, 1998; Casas et al, 1999; Warren et al, 2000; Cinca et al, 2008). Quite recently, the use of refined fast broadband electrical impedance spectroscopy (EIS; Sanchez et al, 2011) allowed to describe the cyclic pattern of systolic-diastolic impedance changes in a swine model of acute myocardial ischemia (Jorge et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, during the healing over process the necrotic scar turns to lower than normal impedance values (Fallert et al, 1993; Wolf et al, 2001; Salazar et al, 2004). In these studies, the technique of measuring the changes in myocardial impedance did not allow to delineate the sequential impedance variations elicited during the systole and diastole phases of the cardiac cycle because of the long time required for the whole impedance spectrum acquisition (Gersing, 1998; Casas et al, 1999; Warren et al, 2000; Cinca et al, 2008). Quite recently, the use of refined fast broadband electrical impedance spectroscopy (EIS; Sanchez et al, 2011) allowed to describe the cyclic pattern of systolic-diastolic impedance changes in a swine model of acute myocardial ischemia (Jorge et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In cardiac tissue characterization applications, electrical impedance spectroscopy (EIS) has been used to detect acute ischemia [2], [3], old infarction scar [4] and rejection in transplanted heart [5], [6]. Measurements are performed in open thorax set-ups [3], through catheter [3], [4] or using a pacemaker-type device [5], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Again, this result is comparable to the literature that resistivity value for randomly-oriented human heart muscle in the range of 200-600 Ωcm depending on the temperature & applied frequency setting in experiments. [38,[40][41][42] It was clearly shown that with the incorporation of cells, the resistivity of the construct was significantly reduced from 616.01±141.08Ω to 359.77±40.96Ω) (p=0.0023). The conductivity of the construct was improved from 2.37x10 -3 Ω -1 cm -1 to 4.17x10 -3 Ω -1 cm -1 , proving that the presence of cells facilitate electrical propagation.…”
Section: Electrical Properties Of Reseeded Ecmmentioning
confidence: 96%
“…[22] Physiological voltage across myocardium has been reported in the range of 3-8V with the resistivity reported to be in the range of 200-600 Ωcm depending on the temperature & applied frequency setting in experiments. [38][39][40][41][42]…”
Section: Electrical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation